Project Based Learning Model: Can It Improve Dribbling Skills In Soccer Games? - Riyan Hardinata; Ghana Firsta Yosika; Youssouf Haïdara; Rahmat Putra Perdana; Uray Gustian; Didi Suryadi; Makan Sacko; Muhamad Zainal Abidin (Indonesian Journal of Physical Education and Sport Science)
Study purpose. The ability to dribble is a very important skill in soccer, because dribbling skills in soccer aim to be able to pass opponents so that players have the opportunity to provide bait. However, there are still many students who have difficulty in dribbling in soccer games.